Asthma - Arshad, S. Hasan (Facts (Oxford, England), 2009)
From the Publisher: Asthma is a common chronic inflammatory condition of the airways which causes coughing, wheezing, shortness of breath and tightness of the chest. Asthma attacks can be triggered by exposure to allergens, physical exertion, stress, or can be aggravated as a result of common coughs and colds. Over 5 million people in the UK and over 6% of children in the US suffer from Asthma, and a recent increase in prevalence is thought to be attributed to our modern lifestyle, such the changes in housing, diet and a more hygienic environment that have developed over the past few decades. Asthma: The Facts is a practical guide to asthma, suitable for those who suffer from asthma, their families, and the health professionals that treat them. It details how a diagnosis of asthma is reached, and what treatments are available to successfully manage the condition and prevent attacks on a day-to-day basis. The book contains advice on proactive changes which can be made to lifestyles, such as avoiding allergens, as well as how to cope with an attack, and how to administer the relevant treatment effectively. The authors conclude that whilst there is currently no cure for asthma, by taking a proactive, self-directed approach to management, its impact on the patient and their lives can be significantly reduced.